Levantamento, flutuação e análise entomofaunística em mata remanescente da Zona da Mata, Viçosa, Minas Gerais. I. Sphingidae: Lepidoptera - Fiuza Ferreira, Paulo Sérgio; dos Santos Martins , David; Hubner, Norival (Revista Ceres, 2025)
A survey and faunistic analysis of the moths of the family Sphingidae (Insecta: Lepidoptera) was carried out in a relict forest of Zona da Mata in the Region of Viçosa, Minas Gerais. A total of 102 weekly samples were collected from August, 1981 to August, 1983 by means of a light trap with an ultraviolet lamp.